In vitro antiviral activity of Vanillosmopsis arborea Baker against dengue virus - Lana Karine Vasconcelos Barroso; Lucas Lucena Martins; José Galberto Martins da Costa; Antonio Eufrásio Vieira-Neto; Léo Santiago; Danielle Malta Lima; Adriana Rolim Campos (Elsevier, 2023)
Background/Purpose: Dengue fever is a tropical, endemic infectious disease. The lack of specific treatment has spurred interest in the search for medicinal plants with activity against the dengue virus (DENV). In this study we evaluated the antiviral activity in vitro of essential oil of Vanillosmopsis arborea (Gardner) Baker(EAEO), an essential oil rich in (-)-α-bisabolol (BISA). Methods: Using MTT colorimetry, cytotoxicity was evaluated, followed by screening of antiviral activity in three different assays: pre-, post- and virucidal treatment. Results: EAEO presented inhibition in the three assays for DENV-2 and DENV-3, except for DENV-3 in the pretreatment. Molecular docking study confirmed by the high specificity of BISA for Protein E from DENV2 and intermediate specificity in relation to Protein E from DENV3. Conclusions: Our study identified one plant species (rich in (-)-α-bisabolol) with promising antiviral property against dengue virus.